Evaluating English Language Instruction Using the Smart Unilak System: A Student-Based Longitudinal Analysis (2018-2024) - Indah Muzdalifah; Dafwen Toresa; Fana Wiza; Vivi Indriyani (STAI Hubbulwathan Duri, 2025)
Evaluation and assessment play vital roles in language acquisition and overall teaching effectiveness. Despite their importance, research on English language instruction evaluation in Indonesian universities remains scarce. Many lecturers resist classroom evaluation, often viewing teaching as merely delivering content without ongoing reflection or feedback mechanisms. This study uses a quantitative descriptive approach to analyze archival student feedback data collected through an e-learning platform’s questionnaire feature. The research focuses on one lecturer teaching the MKDU English course since 2016, involving 57 classes across 9 study programs from 4 faculties: Engineering, Agriculture, Business, and Law. The questionnaire, consisting of 26 items, served as a reliable instrument for evaluating classroom instruction. Over six years, the lecturer consistently received scores ranging from 4 to 5 on a Likert scale, translating to